2001
DOI: 10.1039/b100119l
|View full text |Cite
|
Sign up to set email alerts
|

A method for the measurement of catechol-O-methyltransferase activity using norepinephrine, an endogenous substrate

Abstract: We propose a highly sensitive method for the measurement of catechol-O-methyltransferase (COMT) activity with norepinephrine (NE), an endogenous native substrate. The product, normetanephrine, was determined by high-performance liquid chromatography (HPLC)-peroxyoxalate chemiluminescence reaction detection or, if required, less sensitive fluorescence detection. For the measurement of membrane-bound (MB)-COMT activity in the rat erythrocyte, the HPLC-peroxyoxalate chemiluminescence reaction detection was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…There were no differences in the affinity for NE in both isozymes. In both SHR and WKY rats, the Km values for NE in S-COMT were about 80 times higher than those in MB-COMT, which is in agreement with the previous reports (13,14,17). The Vmax/Km values, i.e., the specificity constant values were calculated based on the above data.…”
Section: Km Values For Ne In the Liversupporting
confidence: 74%
See 1 more Smart Citation
“…There were no differences in the affinity for NE in both isozymes. In both SHR and WKY rats, the Km values for NE in S-COMT were about 80 times higher than those in MB-COMT, which is in agreement with the previous reports (13,14,17). The Vmax/Km values, i.e., the specificity constant values were calculated based on the above data.…”
Section: Km Values For Ne In the Liversupporting
confidence: 74%
“…The general procedure for the COMT activity measurement in tissues and erythrocytes was similar to that previously described (13,14). Tissues were removed from anesthetized rats, weighed, and homogenized in homogenizing buffer (50 mmol/l sodium phosphate buffer (pH 7.5) with 0.5 mmol/l dithiothreitol).…”
Section: Comt Activity and Kinetics Measurementmentioning
confidence: 99%
“…It is plausible that these organs may play an important role in the removal of circulating catecholamines and/or other catechol compounds. Previously, to obtain information on the metabolism of catecholamines in vivo, we have developed a method for COMT activity measurement in rat erythrocytes and human erythrocytes with HPLCfluorescence or chemiluminescence detection (Tsunoda et al, 2001a;Masuda et al, 2002). Here, using this method, we report the optimized conditions for COMT activity measurement in rat liver and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, we reported a sensitive determination method of COMT activity in rat erythrocytes and human erythrocytes (Tsunoda et al, 2001a;Masuda et al, 2002). The method included on-line extraction of amines, separation on an ODS column, electrochemical oxidation to their respective o-quinones, fluorogenic derivatization with ethylenediamine and fluorescence or peroxyoxalate chemiluminescence reaction detection.…”
Section: Introductionmentioning
confidence: 99%
“…13 In contrast, other studies using artificial substrates such as DBA and 2-(3,4-dihydroxyphenyl)naphtha-[1,2-d]thiazole showed that there was no difference in affinities for the substrates between S-COMT and MB-COMT.7.9.1(' Therefore, it is reasonable to expect that the results obtained by our present assay using NE, a natural substrate, reflected more physiological performance of S-and MB-COMT in the human body.…”
Section: Catechol·o·methyltransferase Activities In Human Erythrocytesmentioning
confidence: 99%